AN EXPOSITION ON SPECTROPHOTOMETRIC DETERMINATION OF PLATINUM GROUP METALS - Arora, Tanu; Agnihotri, Nivedita; Azam, Mohammad (Journal of the Chilean Chemical Society, 2025)
In the realm of analytical chemistry, transition metal complexes especially the platinum group metals (PGMs) are often used compounds. Strong chromophores, inflexible luminous structures, biological potential and electrochemical activity are characteristics of the platinum metal complexes. These features have prompted the creation and study of analytical techniques based on these metal complexes for the identification of different analytes in a variety of analytical applications. Even if there are a few broad recommendations accessible to forecast a reagent’s potentialities for the given goal, these studies show that sensitivity and selectivity imparted by the reagent to the metal in respective complex must be established. The quest for novel reagents is an ongoing effort to the wide and varied need for new ways to identify and analyze the metal ions under the peculiar conditions. In light of the frightening and complicated issue of environmental contamination, the endeavor of developing new and innovative reagents as well as techniques for inorganic analysis of PGMs have particular relevance. Of the numerous methodologies, the UV/VIS spectrophotometric determination technique of the PGM complexes is of interest being reliable, easy to handle, quick, cost effective, selective and sensitive. The technique relies on the process of interaction between an analyte and the metal, which are then determined analytically. In light of the enrichment of platinum group metals, the purpose of this article is to outline current research in the methods of spectrophotometric determination of PGMs. The review will assist researchers in formulating and refining PGMs as workable candidates for applications in medicine, pharmacology, analysis and catalysis.